Current System of Banking: An Analysis in Reference of Capital Raipur of Chhattisgarh State - Gupta, Ruchi; Kashyap, Sunil Kumar (International Journal of Computer Sciences and Engineering, 2025)
The proposed work is based on questionnaire base primary data and its analysis through numerically and linguistically terminology. The resultant is found as banking is an optimized principle known by the public as per essential but not as generalized. This paper proposed a new model of banking for the future prospective. We presented a new function based on economical & transaction application. There are some variants in banking found in the paper. These e variants will be formulated for the future banking is suggested as the resultant